Tinjauan Yuridis Tentang Perjanjian Kerjasama Endorsement Antara Influencer Dengan Online Shop Ditinjau Dari Kuhperdata Dan Uu Ite - Aal Fachru Rozi Ardhana (Publikasi Indonesia, 2025)
With the advancement of time and the increasing number of methods for promoting products, online shop owners now have greater freedom to choose promotional services from influencers. An endorsement agreement is a contract made between an online shop owner and celebrities or popular social media personalities with a significant following, aimed at promoting the products or services offered by the online shop owner. These agreements are commonly made informally and are often executed electronically. In relation to this, the study aims to examine the validity, binding force, and legal consequences of Endorsement Cooperation Agreements between Influencers and Online Shops as reviewed under Book III of the Indonesian Civil Code (KUHPerdata) and the Electronic Information and Transactions Law (UU ITE). The research addresses this issue using descriptive research specifications, a normative juridical approach, and primary legal materials including the Civil Code and other relevant laws, secondary legal materials such as expert books, and tertiary legal materials including legal dictionaries and language dictionaries. The analysis is conducted through legislative and conceptual approaches, with data collected via document studies and literature reviews, and analyzed using qualitative methods with a descriptive analytical approach. The research findings on the first issue indicate that endorsement cooperation agreements between influencers and online shops are valid and legally binding, meeting the requirements for a valid agreement under both the Civil Code and the regulations on electronic contracts in the Electronic Information and Transactions Law, despite differences in age competency. For the second issue, the legal consequences under the Civil Code state that if the agreement does not meet the requirements for validity, it may be annulled and rendered void by law.